Credit Spreads and Business Cycle Fluctuations - Gilchrist, Simon; Zakrajšek, Egon (American Economic Review, 2012)
Using micro-level data, we construct a credit spread index with considerable predictive power for future economic activity. We decompose the credit spread into a component that captures firm-specific information on expected defaults and a residual component–– the excess bond premium. Shocks to the excess bond premium that are orthogonal to the current state of the economy lead to declines in economic activity and asset prices. An increase in the excess bond premium appears to reflect a reduction in the risk-bearing capacity of the financial sector, which induces a contraction in the supply of credit and a deterioration in macroeconomic conditions.